Law Enforcement on The Practice of Thuggery in Indramayu Regency - Arief Rachman Maulana; Dimas Furwanto; Virlie Meylody; Sri Primawati Indraswari; Gunadi Rasta (Rechtsnormen: Journal of Law, 2025)
Background. Thuggery is increasingly prevalent in every social activity. Not only does it cause fear in the community, but the practice of thuggery is also the cause of the decline in the level of public trust in Law enforcement. The study formulates the problem by examining how the modus operandi is often used in the practice of thuggery in Indramayu Regency and how law enforcement can overcome the practice of thuggery. Purpose. This study aims to analyze the modus operandi used in thuggery activities and understand and evaluate law enforcement's effectiveness in thuggery. Methods. The research method used is Empirical Jurisprudence. Direct observation was carried out in areas with a relatively high level of thuggery in Indramayu Regency. Result. The study's results show that one mode of thuggery often encountered in Indramayu Regency is Illegal Levy under the pretext of selling mineral water. Conclusion. Law enforcement consists of several aspects, such as the legal factors themselves, law enforcement factors, facilities and facilities factors, community factors, and cultural factors.   Implementation. Law enforcement is strengthened by increasing legal awareness in the community and implementing stricter sanctions to reduce the practice of thuggery in the future.